2020
DOI: 10.1159/000512976
|View full text |Cite
|
Sign up to set email alerts
|

The Eya1 Phosphatase Mediates Shh-Driven Symmetric Cell Division of Cerebellar Granule Cell Precursors

Abstract: During neural development, stem and precursor cells can divide either symmetrically or asymmetrically. The transition between symmetric and asymmetric cell divisions is a major determinant of precursor cell expansion and neural differentiation, but the underlying mechanisms that regulate this transition are not well understood. Here, we identify the Sonic hedgehog (Shh) pathway as a critical determinant regulating the mode of division of cerebellar granule cell precursors (GCPs). Using partial gain and loss of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 79 publications
(116 reference statements)
0
11
0
Order By: Relevance
“…This has all been called into question by a study suggesting that interaction between EYA3 and PP2A is responsible for the threonine phosphatase activity previously attributed to the EYA3 N-terminal domain [16]. However, a more recent report failed to detect any PP2A during the EYA1-mediated dephosphorylation of Thr410 of aPKCζ [38]. This could possibly be ascribed to differences between EYA3 and EYA1.…”
Section: Eya Cellular Functions and Substratesmentioning
confidence: 99%
“…This has all been called into question by a study suggesting that interaction between EYA3 and PP2A is responsible for the threonine phosphatase activity previously attributed to the EYA3 N-terminal domain [16]. However, a more recent report failed to detect any PP2A during the EYA1-mediated dephosphorylation of Thr410 of aPKCζ [38]. This could possibly be ascribed to differences between EYA3 and EYA1.…”
Section: Eya Cellular Functions and Substratesmentioning
confidence: 99%
“…The N-terminal domain of the EYA proteins has an independent transactivation function localized to a Pro/Ser/Thr-rich ∼210 amino-acid segment in Drosophila Eya [16]. In addition, a threonine phosphatase activity (either intrinsic or via interaction with protein phosphatase 2A (PP2A)) is associated with the N-terminal domain [17][18][19][20][21][22].…”
Section: Eya Protein Architecture and It's Placement In The Rdgnmentioning
confidence: 99%
“…A Shh-Eya1 axis is also involved in promoting symmetric cell divisions during cerebellar development [22]. This is believed to occur through dephosphorylation of Thr410 and thus inactivation of the atypical protein kinase aPKCζ [22], once again implicating an EYA-linked threonine phosphatase activity in development.…”
Section: Eya Proteins In Other Developmental Contextsmentioning
confidence: 99%
“…Its function as transcriptional coactivator may be modulated by its tyrosine phosphatase activity in some contexts ( Li et al, 2003 ). In addition, Eya protein also binds directly to other proteins and serves as a phosphatase in either the nucleus or the cytoplasm, but these functions are still poorly characterized ( Fan et al, 2000 ; Li et al, 2003 ; Embry et al, 2004 ; Cook et al, 2009 ; Krishnan et al, 2009 ; Xiong et al, 2009 ; Ahmed et al, 2012a , b ; Merk et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent evidence suggests that Eya1 may also affect the balance between proliferating progenitors and differentiating neurons in Six1-independent ways and possibly by acting in the cytoplasm. In the cerebellum, Eya1 has been shown to directly dephosphorylate cell polarity proteins such as atypical protein kinase C (aPKC), thereby affecting apicobasal cell polarity and changing the balance between proliferating and differentiating cells by controlling the proportion between symmetric and asymmetric cell divisions ( Merk et al, 2020 ). Another study ( El Hashash et al, 2011 ) reported a similar role of Eya1 in the lung epithelium but was subsequently retracted ( El Hashash et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%